2020
DOI: 10.3390/agronomy10020304
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Tillage Systems on Productivity of Narrow-Leaved Lupin-Winter Wheat-Winter Triticale-Winter Barley Rotation

Abstract: Legumes are increasingly important crops in most European Union (EU) countries because of the growing demand for feed protein, and also because they have been shown to improve the characteristics of soil. The main part of the crop rotation is taken up by cereals, but they are connected with undesirable side effects, such as the unilateral utilization of ingredients and the heightened risk of plant diseases, e.g., Fusarium. Simplification of farming methods has become increasingly popular as growers search for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Moreover, according to the authors, a more diverse mix of CCs (14 species) does not outperform a less diverse mix. Research by Panasiewicz et al [167] with narrow-leaved lupine in crop rotations with 75% cereal composition also indicate that the method of tillage has a significant influence on weed infestation and consequently, the seed yield. Dry weigt of weeds under conventional tillage was significantly lower than in reduced tillage and no-tillage.…”
Section: Effect Of Legume Ccs Cultivation Systems On Weed Controlmentioning
confidence: 94%
“…Moreover, according to the authors, a more diverse mix of CCs (14 species) does not outperform a less diverse mix. Research by Panasiewicz et al [167] with narrow-leaved lupine in crop rotations with 75% cereal composition also indicate that the method of tillage has a significant influence on weed infestation and consequently, the seed yield. Dry weigt of weeds under conventional tillage was significantly lower than in reduced tillage and no-tillage.…”
Section: Effect Of Legume Ccs Cultivation Systems On Weed Controlmentioning
confidence: 94%
“…The reason for the decrease in winter wheat yield is probably due to the amount of rainfall during the growing season (May-July) in both years: 689 and 149.5 mm, respectively. Many authors have reported substantial changes in the yield of winter wheat caused by differences in fertilization rates, climatic conditions and crop rotation [23,[27][28][29]. Total N in the winter wheat harvested in 2018 amounted to 93.2 kg ha −1 in the control subplots and 146.6 kg in the N-fertilized subplots.…”
Section: High Content Of Nomentioning
confidence: 99%
“…Such strong functional relations were also found in barley plants in the reduced system between total nitrogen content in post-harvest residues (%) and grain yield and total biomass yield (Figure 1). In a study carried out by Panasiewicz et al [40], the protein content ranged from 295 g kg −1 in conventional tillage to 314 g kg −1 in no-tillage (direct sowing) and the tillage system did not influence the protein content in narrow-leaved lupin seeds. However, there was a trend of increasing protein content in seeds as the tillage system became more minimized.…”
Section: Tionmentioning
confidence: 94%